CRITICAL REVIEW ON THE ROLE OF TECHNICIANS AND SPECIALISTS IN ENHANCING EMERGENCY MEDICAL SERVICES - 1Saeed Abdullah Moaed Alhamamah, 2Abdullah Hamad Jaber Al Thaiban, 3Hajar Salah EidAlkhaldi, 4Bader Saeed Alqshanin, 5Hassan Ali MaedAlhamamah, 6Mana Mahdi Mana Alyami, 7Saleh Hamad Al-Qalyan, 8Mohammad Ali Mohammad Al Hammam, (Chelonian Research Foundation, 2022)
Emergency Medical Services (EMS) rely heavily on the expertise of technicians and specialists to provide timely and effective care to patients in critical situations. This paper critically examines the pivotal role played by technicians and specialists in enhancing EMS. Through a comprehensive literature review, various aspects of their contributions are explored, including their training, skillsets, and impact on patient outcomes. Methodologies for assessing their effectiveness are analyzed, along with empirical evidence from studies utilizing figures, tables, and graphs. The discussion encompasses the challenges faced by technicians and specialists, as well as potential solutions for improving their efficiency in EMS. The conclusion emphasizes the indispensable nature of their roles and offers recommendations for further enhancing their contributions to emergency medical care. Keywords: Emergency Medical Services, technicians, specialists, training, patient outcomes, effectiveness